2011
DOI: 10.1080/11745398.2011.615717
|View full text |Cite
|
Sign up to set email alerts
|

Masculinities, affect and the (re)place(ment) of stardom in Formula One fan leisure practices

Abstract: Writing from an autoethnographic perspective, this article explores male leisure practices via the mediated relationships fans enter into with stars. More specifically, my own fandom for Formula One driver Jacques Villeneuve is the locus of study, revealing how this affective investment shapes and furnishes my corresponding leisure practices. Notions of gendered 'performativity' come to the fore, with my own displays evoking, enacting and revealing oscillating performances of masculinity. Moreover, there are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The notions of affective attachment, investment and loyalty, mattering maps, and intensities noted by Hall et al (2012) and Sturm (2011) has clear links with the affective dynamics of the narrative habitus as described by Frank (2010) in relation to how people feel in, and through, their bodies about the repertoire of stories made available to them by the cultures they inhabit and also how such stories perform as actors in their lives. One such story that circulates within Western cultures and invites affective attachments, investments and loyalties, as we indicated earlier, is that of the sporting hero, a figure that we now consider.…”
Section: Introductionmentioning
confidence: 88%
“…The notions of affective attachment, investment and loyalty, mattering maps, and intensities noted by Hall et al (2012) and Sturm (2011) has clear links with the affective dynamics of the narrative habitus as described by Frank (2010) in relation to how people feel in, and through, their bodies about the repertoire of stories made available to them by the cultures they inhabit and also how such stories perform as actors in their lives. One such story that circulates within Western cultures and invites affective attachments, investments and loyalties, as we indicated earlier, is that of the sporting hero, a figure that we now consider.…”
Section: Introductionmentioning
confidence: 88%
“…Such greenwashing has been shown in wider contexts to be related to commercialization or the socio-economic process of transforming a sport into a business (Sturm 2011) as well as commodification or process by which goods and services with high use value are transformed into marketable products as commodities (Mosco 2009). With respect to the latter, in motor sport this ranges from clothes ware to larger paraphernalia and even drivers as consumer objects (Sturm 2011). Indeed, commodification is also known to extend to the environment, to environmental sustainability and derivatives such as ecotourism and, indeed, professional sport (Dorsey et al 2004).…”
Section: A More Critical View On Environmental Sustainability Marketimentioning
confidence: 99%
“…Drawing upon affect theory, I argue that affective technological relationships can potentially be forged with the televisual innovations, specifically as viewers marvel at the technologies and perspectives being afforded for them. Theoretically, on the one hand, affect is conceived as a broader attachment to objects, places and things, with affect shaping an individual's investment 3 towards and in such things; specifically the levels of invigoration, intensities and energies that are "felt" and enacted (Grossberg, 1992;Sturm, 2011). On the other hand, recent works have suggested that affect articulates the sensations, movements and assemblages that intensify, circulate around and move through such objects, places, spaces and practices (Clough and Haley, 2007;Gregg and Seigworth, 2010).…”
Section: Television Technologies Spectacle and Affectmentioning
confidence: 99%